Pengaruh Religiusitas, Motivasi, dan Tingkat Literasi Pasar Modal Syariah Terhadap Minat Berinvestasi Pasar Modal Syariah - Muhammad Zainal Abrori; Muhammad Hifdil Islam; Nuruddin Armanto (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2023)
This study aims to determine the influence of religiosity, motivation, and literacy of the Islamic capital market partially and simultaneously on the investing interest in the Islamic capital market of ISP members in Probolinggo. This study used multiple regression analysis techniques titled "The Influence of Religiosity, Motivation, and Literacy Level of the Islamic Capital Market on Investment Interest in the Islamic Capital Market" using an associative quantitative method. The data sources were derived from questionnaires distributed to 74 samples by purposive sampling techniques. The analysis techniques used are multiple linear regression analysis, determination coefficient test, F-test, and T-test processed with SPSS. The F-test results showed religiosity, motivation, and literacy of the Islamic capital market has significance compared with a calculated F-value of 50,987 an F-table of 2,736, and a significance of 0.000. Meanwhile, the T-test result showed religiosity, motivation, and literacy levels each influence the sig value by 0.031, 0.016, and 0.000.